2020
DOI: 10.3390/ijms21041255
|View full text |Cite
|
Sign up to set email alerts
|

RhoA/ROCK Regulates Prion Pathogenesis by Controlling Connexin 43 Activity

Abstract: Scrapie infection, which converts cellular prion protein (PrPC) into the pathological and infectious isoform (PrPSc), leads to neuronal cell death, glial cell activation and PrPSc accumulation. Previous studies reported that PrPC regulates RhoA/Rho-associated kinase (ROCK) signaling and that connexin 43 (Cx43) expression is upregulated in in vitro and in vivo prion-infected models. However, whether there is a link between RhoA/ROCK and Cx43 in prion disease pathogenesis is uncertain. Here, we investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…It has been suggested that GJIC is reduced via RhoA-mediated Cx43 phosphorylation and Cx43/ZO-1/drebrin complex instability-mediated Cx43 degradation [ 97 ]. Curiously, in prion-infected neurons, RhoA seems to interact with Cx43, with RhoA/ROCK inhibition blocking Cx43 hemichannel activity [ 98 ]. In agreement with this hypothesis, previous work strongly suggested that RhoA activation is a key player in thrombin-induced inhibition of Cx43 hemichannel activity [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that GJIC is reduced via RhoA-mediated Cx43 phosphorylation and Cx43/ZO-1/drebrin complex instability-mediated Cx43 degradation [ 97 ]. Curiously, in prion-infected neurons, RhoA seems to interact with Cx43, with RhoA/ROCK inhibition blocking Cx43 hemichannel activity [ 98 ]. In agreement with this hypothesis, previous work strongly suggested that RhoA activation is a key player in thrombin-induced inhibition of Cx43 hemichannel activity [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a molecular point of view, the overactivation of ROCKs in neuronal stem cells and mature neurons infected with prions, affect the neuronal polarity and connectivity by altering the dynamics of both FAs and the actin cytoskeleton, the latter being necessary to sheath the axon and to stabilize the synaptic button (Figures 3A,B). Beyond in vitro neuronal cell models, ROCKs oversignaling was also evidenced in vivo in the brain of prion-infected mice according to cofilin overphosphorylation (Alleaume-Butaux et al, 2015;Kim et al, 2020) and was confirmed by a kinomics approach (Shott et al, 2014). In 2018, Zafar et al provided evidence for altered cofilin and deregulation of upstream regulators (ROCK-2, LIMK1) in the cortex and cerebellum of humans with sporadic Creutzfeldt-Jakob disease (Zafar et al, 2018).…”
Section: Prion Infection Rock Oversignaling and Polarity Alterationsmentioning
confidence: 95%
“…RhoA, one family member of the Rho-GTPases, plays a key role in cell remodeling 20 through activation of ROCKs and its interactions with different connexins has been described in other cell types 21,22 . We thus tested the activation of RhoA by assessing levels of RhoA-GTP using immunohistochemistry, and found a strong increase in KD mice (Fig.…”
Section: Astroglial Cx30 Closes the Critical Period By Downregulatingmentioning
confidence: 99%